The bet Paul Ehrlich, Julian Simon, and our gamble over Earth's future - Sabin, Paul, 1970- (Yale University Press, 2013)
"The Bet uses a legendary wager between the Stanford biologist Paul Ehrlich and the conservative University of Illinois economist Julian Simon to examine the roots of modern environmentalism and its relationship to broader political conflicts in the nation. Ehrlich, author of the landmark 1968 book The Population Bomb, believed that rising populations would cause overconsumption, scarcity, and disastrous famines. Simon countered that flexible markets, technological change, and human ingenuity would allow societies to adapt to changing circumstances and continue to improve human welfare. In 1980, they made a much-ballyhooed bet about the future prices of five metals that served as a proxy for their arguments about the future. The Bet weaves intellectual biographies of Ehrlich and Simon into the history of late twentieth-century environmental politics and other struggles of the era between liberals and conservatives. Humanity's larger gamble on the future still remains unresolved. By wrestling with the different sides of these arguments, The Bet encourages a more nuanced approach to environmental problems, one that acknowledges the limitations of both ecology and economics in guiding policy, and that instead emphasizes the conflicting values that underlie political choices. The Bet is structured around three bets: first, the $1000 bet that Ehrlich (and two colleagues) made with Simon over the prices of chromium, copper, nickel, tin, and tungsten; second, the bet that the United States faced in the 1980 presidential election in choosing between Carter and Reagan; and third, the larger gamble that we as a society continue to make as we make choices"--